Fostering Environmentally Conscious Purchasing Through Ecological Promotion: How Gender and Ecological Awareness Play a Role at Pizza Hut: Mendorong Konsumsi Berkelanjutan Melalui Green Marketing: Pengaruh Gender dan Pengetahuan Lingkungan di Pizza Hut - Steven; Hommy Dorthy Ellyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The purpose of this research was to ascertain the connection between sex and their awareness of ecological issues in relation to purchasing decisions that promote sustainability, as well as the employment of environmentally friendly marketing strategies. In addition, this research endeavors to discover if ecological marketing can regulate the effects of both gender and ecological awareness on the encouragement of sustainable purchasing habits. One hundred participants were chosen for the study, all of whom had bought items from the Gajah Mada Medan branch of Pizza Hut while the study was being conducted; the exact number of respondents was not known. Purposive sampling was the method utilized in the selection of the sample. The findings of the study demonstrated that there was a substantial and favorable association between one's gender and their acceptance of green marketing strategies; that there was a considerable and favorable association between one's ecological awareness and their acceptance of green marketing strategies; that there was a substantial and favorable association between one's gender and their adoption of sustainable consumption habits; that one's ecological awareness had no bearing on their adoption of sustainable consumption habits; that there was a substantial and favorable association between the use of green marketing and the promotion of sustainable consumption; that green marketing was able to act as a mediator in the connection between one's gender and their engagement in sustainable consumption; and that green marketing was unable to act as a mediator in the connection between one's ecological awareness and their engagement in sustainable consumption.